Emotional Intelligence Skills: Is Nurses' Stress and Professional Competence Related to their Emotional Intelligence Training? A quasi experimental study - Aghajani Inche Kikanloo, Afagh; Jalali, Kataouon; Asadi, Zahra; Shokrpour, Nasrin; Amiri, Maliheh; Bazrafkan, Leila (Journal of advances in medical education & professionalism, 2019)
Emotional intelligence is a social skill that controls stress and affects one's ability to cope with the demands and environmental pressures; it so can improve professional competence in health care providers such as nursing students. Training on emotional intelligence increases the mental health and influences the mutual relationships, stress, depression and aggression. This study aimed to determine the effect of emotional intelligence skills training program on the stress and academic success of nursing students in a higher education health complex. This study is a quasi-experimental study with an educational intervention. The participants included 100 students of nursing selected by stratified random sampling from both genders. They were randomly categorized into two intervention and control groups including 50 subjects, respectively. We used Meyer and Salvia model in Emotional Intelligence training in the intervention group. During the training sessions in the intervention group, the control group did not receive any intervention. Academic stress and professional competence in both groups were measured before and two weeks after the experiment. SPSS version 21 was used to analyze the data, using Paired t-test, independent t-test, Wilcoxon, Mann-Whitney and Chi-Square tests. The mean age of the participants was 20 ± 2.14 years old. According to the results, the mean difference of the changes in the professional competence (P<0.001), total academic stress (P<0.001), and the four areas of academic stress such as emotional response (P<0.001), physical response (P<0.001) and physiological response (p<0.001) were significant. The intervention group, as compared with the control group, showed no significant effect on the other factors of academic stress such as frustration, conflict, academic pressure, changes and self-imposed stress. The education of emotional intelligence components can improve the efficiency of nursing care services and professional competence due to deceased stress.